Antidiabetes of Combination of Fractionated-extracts of Andrographis paniculata and Centella asiatica in Neonatal Streptozotocin-induced Diabetic Rats - Reni Ariastuti; La Ode Muhammad Fitrawan; Agung Endro Nugroho; Suwidjiyo Pramono (Universitas Gadjah Mada, 2020)
Many medicinal plants are widely grown in South- and Southeast Asia countries. Some of them are traditionally used for treatment of diabetes mellitus such as Andrographis paniculata and Centella asiatica. In the study, we provided fractionated-extracts of A. paniculata and C. asiatica to increase the concentration of their active compounds and eliminate unexpected substances. The aim of the study was to evaluate the antidiabetes effect of the combination of their fractionated-extracts in male neonatal streptozotocin (STZ)-induced diabetic rats. In the study, diabetes was injected intraperitoneally 90mg.kg-1 BWSTZ  to two day-old rats. At the age of three months, the rats were administered with the combination of both fractionated-extracts for 14 consecutive days. We evaluated antidiabetes with parameters of blood glucose levels, morphology of pancreatic islet, β-cell density as well as immunohistochemical pancreatic insulin. The levels of MDA, SOD and GPx were also determined about oxidative stress change after treatment with the combination. In the study, the combination succeeded to lower the blood glucose level in neonatal STZ-induced diabetic rats. Inline with fact, improvement of rat pancreatic islets and β cells density, as well as moderate restoration of pancreatic insulin, were observed after treatment with the combination. The substance could decrease the level of MDA, and increase the levels of SOD and GPx. In conclusion, the combination of fractionated-extracts of A. paniculata and C. asiatica exhibited potential antidiabetic effect to its antioxidative effect in male neonatal STZ-induced diabetes rats.